2002
DOI: 10.1149/1.1452114
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Reactions Between Delithiated Lithium Nickelate and Electrolyte Solutions

Abstract: Lithium nickelate is a promising electrode material for lithium-ion batteries, however, its low thermal stability is a problem that should be solved. We studied the thermal stability of delithiated lithium nickelate compounds in the presence of electrolyte solvents/solutions. We measured the exothermal heat generation of the reaction system using differential scanning calorimetry. We examined simple systems such as ethylene carbonate with Li 0.2 NiO 2 , using hermetically sealed pans that allowed us to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 31 publications
0
67
0
Order By: Relevance
“…A sharp exotherm was observed at 225°C followed by a limited but more sustained reaction at 300°C that may have resulted from electrolyte or binder decomposition. Reactions of the partially reacted cathode with electrolyte have also been reported in this temperature region for similar metal oxides [13,14]. The cathode material showed a strong exothermic between 170°C and 190°C, which corresponds to the explosive decomposition regime seen in the thermal ramp experiments.…”
Section: Gen1 Electrolyte and Electrode Reactions -Arc Bomb Runsmentioning
confidence: 53%
See 3 more Smart Citations
“…A sharp exotherm was observed at 225°C followed by a limited but more sustained reaction at 300°C that may have resulted from electrolyte or binder decomposition. Reactions of the partially reacted cathode with electrolyte have also been reported in this temperature region for similar metal oxides [13,14]. The cathode material showed a strong exothermic between 170°C and 190°C, which corresponds to the explosive decomposition regime seen in the thermal ramp experiments.…”
Section: Gen1 Electrolyte and Electrode Reactions -Arc Bomb Runsmentioning
confidence: 53%
“…The Sony cathode material (LiCoO 2 ) showed the greatest thermal stability with a peak reaction temperature around 225°C. The nickel containing Gen1 cathode material was less stable than the pure cobalt material while the Gen2 cathode (LiNi 0.8 Co 0.15 Al 0.05 O 2 ) was more stable than the Gen1 material (LiNi 0.85 Co 0.15 O 2 ) [13][14][15]. The aluminum doping achieves a small but measurable increase in thermal stability as determined by DSC.…”
Section: Dsc Gen2 Cell Componentsmentioning
confidence: 96%
See 2 more Smart Citations
“…Work by Dahn and coworkers demonstrated that most cathode chemistries decompose and evolve oxygen. 74 Data on oxygen evolution at elevated temperature have been published for LiCoO 2 , 75 LiNiO 2 , 76 and LiMn 2 O 4 . 77 Oxygen production during high-temperature cathode decomposition is correlated with exotherms observed in ARC experiments.…”
Section: Cathodes In Li-ion Batteriesmentioning
confidence: 99%